Efficacy and safety of pemafibrate versus bezafibrate in coronary artery disease patients receiving statin treatment: a randomized, open-label, cross-over study. (3rd October 2022) - Nakamura, A; Kagaya, Y; Saito, H; Kanazawa, M; Sato, K; Miura, M; Kondo, M; Endo, H
Abstract: Background: Fibrates activate peroxisome proliferator-activated receptor (PPAR)-α which is associated with lipid metabolism. Bezafibrate is a non-selective PPAR-α agonist, whereas pemafibrate has been developed as a higher selective PPAR-α agonist. Objective: The efficacy and safety of pemafibrate for 24-week in patients with dyslipidemia was examined in comparison with bezafibrate. Methods: Sixty patients with hypertriglyceridemia (fasting triglyceride (TG) level of ≥150 mg/dL) were treated with pemafibrate of 0.2 mg/day or bezafibrate of 400 mg/day for 24-week in a randomized cross-over study. Percent change from baseline in TG levels was the primary endpoint, and that in HDL-C and apolipoprotein A-I (Apo A-I) levels was the secondary endpoints. Results: A significantly greater reduction in TG percent change was observed in pemafibrate than in bezafibrate (−46.1% vs. −34.7%, p<0.001). There was no significant difference in HDL-C percent change between pemafibrate and bezafibrate (18.4% vs. 14.0%, p=0.067), whereas Apo A-I percent change was significantly greater in pemafibrate than in bezafibrate (9.2% vs. 5.7%, p=0.018). Pemafibrate and bezafibrate significantly decreased alanine aminotransferase (ALT) and gamma-glutamyltransferase (γ-GT) levels, and pemafibrate showed a greater reduction than bezafibrate (ALT: −21.9% vs. −10.6%, p=0.048; γ-GT: −43.5% vs. −33.1%, p=0.025). Creatinine levels significantly increased in both treatments (both p<0.001), however, creatinine percent change was significantly smaller in pemafibrate than in bezafibrate (5.72% vs. 15.5%, p<0.001). There was no difference in frequency of adverse event (AE) or serious AE between two treatments, but frequency of creatinine elevation (≥0.5 mg/d and/or 25%) was significantly higher in bezafibrate than in pemafibrate (16/60 vs. 3/60, p=0.004). Conclusion: As compared with bezafibrate, pemafibrate is more effective to reduce TG levels and to elevate Apo A-I levels, and it is safer in terms of liver and renal function. Funding Acknowledgement: Type of funding sources: None.